Herramientas pedagógicas y su aporte a la comprensión de contenidos científicos área de estudios sociales a estudiantes de la Unidad Educativa Guillermo Baquerizo Jiménez, cantón Babahoyo, Provincia Los Ríos - Gil Galarza, Estela del Pilar (2022)
The present investigative work deals with the use of pedagogical tools and their contribution to scientific knowledge in the area of social studies in the Educational Unit "Guillermo Baquerizo Jiménez", located in the Babahoyo Canton, province of Los Ríos. With the purpose of studying the impact generated by the correct use of the tools, a field investigation was applied which allowed us to make use of qualitative and quantitative methods. Through the application of these tools, the aim is to evaluate the performance of students in learning, thus guaranteeing the continuous training of the class, making it more interactive and comfortable for the student.